Biochemistry cell and molecular biology and genetics - Zeynep Gromley; Gromley, Adam (New york Thieme Medical Publishers, 2021)
Integrates biochemical, molecular, and cellular health and disease processes into one essential text!Biochemistry, Cell and Molecular Biology, and Genetics: An Integrated Textbook by Zeynep Gromley and Adam Gromley is the first to cover molecular biology, cell biology, biochemistry (metabolism), and genetics in one comprehensive yet concise resource. Throughout the book, these topics are linked to other basic medical sciences, such as pharmacology, physiology, pathology, immunology, microbiology, and histology, for a truly integrated approach. Key Highlights. Easy-to-read text enhances understanding of underlying molecular mechanisms of disease. Nearly 500 illustrations and tables help reinforce chapter learning objectives. Textboxes throughout make connections with other preclinical disciplines. End of unit high-order clinical vignette questions with succinct explanations help integrate basic science topics with clinical medicine. This textbook provides a robust review for medical students preparing for courses as well as exams. Dental, pharmacy, physician's assistant, nursing, and graduate students in pre-professional/bridge programs will also find this a beneficial learning tool. This book includes complimentary access to a digital copy on https://medone.thieme.com.